2020
DOI: 10.1002/vms3.260
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Brucella isolates at strain level in Egypt

Abstract: In this study, Multiple Locus Variable Number Tandem Repeat Analysis (MLVA‐16) was performed on 18 Brucella isolates identified bacteriologically and molecularly (AMOS‐PCR) as Brucella abortus ( n = 6) and Brucella melitensis ( n = 12). This was aimed to study the genetic association among some Egyptian Brucella genotypes isolated during the period from 2002 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…These results highlight the high degree of similarity of detected isolates that may indicate the circulation of the same or closely related strains of B. melitensis bv3 in the study region. Similarly, previous studies from Egypt showed high genetic similarity between B. melitensis bv3 isolates in several governorates [ 9 , 14 ]. This similarity of B. melitensis genotypes between different districts in Fayoum governorate may be attributed to free movement of animals between different districts.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These results highlight the high degree of similarity of detected isolates that may indicate the circulation of the same or closely related strains of B. melitensis bv3 in the study region. Similarly, previous studies from Egypt showed high genetic similarity between B. melitensis bv3 isolates in several governorates [ 9 , 14 ]. This similarity of B. melitensis genotypes between different districts in Fayoum governorate may be attributed to free movement of animals between different districts.…”
Section: Discussionsupporting
confidence: 66%
“…In agreement, Brucella was isolated from 7.9% of human cases in Yemen [ 5 ]. The B. melitensis bv 3 is the most predominate species in Egypt [ 13 , 14 ] and the Middle East [ 3 ]. It is also the species most often isolated from cows in Egypt [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains revealed eleven and three genotypes, respectively. Brucella abortus isolates were closely related to Western, Mediterranean, and East Asian strains and clonal lineages from the Americas, and B. melitensis isolates were mostly closer to Western and Eastern Mediterranean clonal lineages [27]. A comprehensive genotyping of 118 Egyptian B. melitensis bv3 utilizing MLVA-16 showed correlation to the West Mediterranean lineage.…”
Section: Discussionmentioning
confidence: 92%
“…At present, 11 species have been identified [1]. Among them, three species have been reported in Egypt; Brucella melitensis isolated from ruminants, Nile catfish, and humans; Brucella abortus isolated from cattle, dogs, and cats; and Brucella suis has been recovered from cattle and swine [2][3][4]. The identification of the Brucellae is done through the direct detection of Brucella organisms in milk, aborted material, lymph nodes, and other tissues through the isolation and typing of the causative microorganism or indirectly using serological tests.…”
Section: Introductionmentioning
confidence: 99%